Feasibility assessment of renewable energies for cassava irrigation in China - Liu, J. (2020)
Based on the irrigational water demand of cassava in an area in Guangxi Province, China, this study compared the supply capacity of hybrid wind/solar power water pumping and that of photovoltaic (PV) water pumping through experiments and calculation. Results show that, the hybrid pumping system supported by a 22kW solar panel and wind turbines of 44kW can fully satisfy cassava’s water demand for irrigation in a 26.66 ha field with surplus energy, so shutdown of wind turbines in the initial stages of cassava growth is suggested. The 22kW photovoltaic water pump alone is not sufficient for a 26.66 ha field, but a 1.5-time larger solar panel (33kW) with an enhanced pump should be able to meet the demand. Considering local uneven distribution of wind power and relative high cost of a hybrid power system, the enhanced photovoltaic water pumping is recommended for popularization.